Japanese public opinion about suspect interviewing techniques - Wachi, Taeko (Legal and criminological psychology, 2019)
Purpose. The new citizen judge system in Japan was implemented in 2009. Further, a revision to the Code of Criminal Procedures, announced in 2016, stipulated that, from 2019, police interviews of suspects tried by citizen judges had to be recorded. Anticipating these changes to the criminal justice system in Japan, this study investigated public perceptions of the various suspect interviewing techniques in use. Methods. A total of 761 jury-eligible Japanese participants completed an online survey that included items about five suspect interviewing techniques (Presentation of Evidence, Confrontation, Active Listening, Rapport Building, and Discussion of the Crime). The participants were asked to rate the fairness of these techniques and the likelihood that they would elicit true and false confessions from guilty and innocent suspects. Results. Participants believed that Active Listening was the fairest of the five interviewing techniques, most and least likely to elicit true and false confessions, respectively. Contrastingly, they viewed Confrontation as the most unfair interviewing technique, least and most likely to elicit true and false confessions, respectively. The fairer the participants perceived the interviewing techniques, the more likely they were to believe these techniques would elicit true confessions. Conclusions. These findings could have important implications for decisions regarding the interviewing techniques used to elicit confessions admitted as evidence in Japanese courts.